Community responses to vulnerable children in rural Zimbabwe: lessons from a partnership case study. Issue 1 (2nd January 2017) - Madziva, Cathrine
ABSTRACT: This article explores a CBO–INGO partnership addressing vulnerable children's needs in rural Zimbabwe. It engages with the global policy consensus that communities are crucial to addressing vulnerable children's needs, alongside questions regarding community existence and definition among the poor. Inhabitants identified a community which was ascertained by a local and community framework. Partnership emerged as possible in the presence of interdependence and when power inequalities are acknowledged as chronically problematic. The INGO's risk-taking, flexibility, and long-term perspective enabled it to go some way in implementing aspects of the partnership, and its emphasis on partner capacity building emerged as desirable.